2013
DOI: 10.3390/su5125135
|View full text |Cite
|
Sign up to set email alerts
|

Learning for the Future? Effects of Education for Sustainable Development (ESD) on Teacher Education Students

Abstract: Currently, politicians, university representatives, scholars and leading NGOs share a strong belief in the ability of educational systems to generate positive attitudes to sustainable development (SD) among citizens, with the idea of Education for Sustainable Development (ESD) as perhaps the most apparent expression of this conviction. The aim of this paper is to investigate whether ESD might have the intended effects on teacher education students. More specifically, we account for the results from a panel stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 26 publications
8
48
0
6
Order By: Relevance
“…Like these prior studies showed, this could be realized by integrating deeper learning experiences instead of only acquiring new knowledge [128]. Concrete examples could include the integration of external stakeholders and real-world experiences in relevant issues in teacher professional development [129][130][131]. These real-world experiences might connect the cognitive input with interdisciplinary characteristics of the issues and needed affective appeals [132].…”
Section: Affective and Ultimately Transformative Teacher Professionalmentioning
confidence: 97%
“…Like these prior studies showed, this could be realized by integrating deeper learning experiences instead of only acquiring new knowledge [128]. Concrete examples could include the integration of external stakeholders and real-world experiences in relevant issues in teacher professional development [129][130][131]. These real-world experiences might connect the cognitive input with interdisciplinary characteristics of the issues and needed affective appeals [132].…”
Section: Affective and Ultimately Transformative Teacher Professionalmentioning
confidence: 97%
“…When the study assesses various kinds of ESD-related courses and activities without such categorization, relationships between the outcomes and specific course or activity becomes unclear. As for the weakness of the quantitative research, it does not reveal the mechanisms behind this change [29]. For instance, how in-school factors of the program contributed to the ESD learning outcomes was not clear from the survey results.…”
Section: Strengths and Weaknesses Of Assessment Approachesmentioning
confidence: 98%
“…The studies conducted in two Swedish universities by Andersson, Jagers, Lindskog and Martinsson (2013) were identified as examples of ESD training. These consisted in evaluating the effects of an ESD course on student teachers.…”
Section: Evaluation Of Training Experiences In Ee and Esdmentioning
confidence: 99%